2022
DOI: 10.19103/as.2022.0104.13
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the health of broiler breeder birds

Abstract: The main objective in broiler breeder production is to produce fertilized eggs resulting in healthy and robust day-old broiler chicks. Due to the continuing increase in the genetic potential of the offspring and the improved reproduction performance, there is a high need for professional management and poultry health care of broiler breeder flocks. Implementation of strict biosecurity measures in combination with intensive, well-orchestrated vaccination programs must prevent disease challenges for both breeder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…Furthermore, it was observed that pullets with 3 h access to water had higher water consumption between 07:30 am and 09:30 am h than did pullets with 5 and 8 h access to water. This rapid drinking during a short period of water access was previously observed in an on-farm study ( van Emous, 2022 ). Breeder pullets with a short period of water access (3 h) are conditioned to consume sufficient water quickly because they have experienced that they will then be deprived of water for a long period of time (21 h).…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Furthermore, it was observed that pullets with 3 h access to water had higher water consumption between 07:30 am and 09:30 am h than did pullets with 5 and 8 h access to water. This rapid drinking during a short period of water access was previously observed in an on-farm study ( van Emous, 2022 ). Breeder pullets with a short period of water access (3 h) are conditioned to consume sufficient water quickly because they have experienced that they will then be deprived of water for a long period of time (21 h).…”
Section: Discussionsupporting
confidence: 75%
“…To prevent wet litter conditions, a restricted amount of water is also provided. Under Nortwest Europe commercial circumstances, water is typically provided for 3 h daily during the rearing phase and for 5 to 7 h daily during the laying phase ( van Emous, 2022 ). Approximately 65% of rearing and breeder farmers apply a maximum time limit on water access, while other farmers apply a maximum amount of water based on a water-to-feed ratio of around 1.8.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation